99 film scenes for actors - Nicholas, Angela (New York Avon Books, 1999)
Looking for a great piece to work on in your scene study class? For an audition? You want something fresh, juicy, well-written--something you haven't seen in every scene book. Give Chekov a rest and run to memorable characters and scenes from the silver screen.

This remarkable anthology offers an incredible range of contemporary dialogues from the pens of the industry's finest talents--scenes that pulsate with emotional life, scenes that live on their own, out of context. Blistering drama and caustic comedy excerpted from the classic screenplays of James L. Brooks and Oliver Stone, and there are cutting-edge scenes of today's films, a wealth of material to motivate any actor--great scenes that will inspire and challenge you.

Within these pages, actors will find emotionally charged scenes from big studio megahits and small gems from acclaimed independent films. Featuring characters ranging from the larger-than-life to low-key introverts, 99 FILM SCENES FOR ACTORS is an cornucopia of cinematic classics for actors eager for their close-up.
Includes indexes (pages 427-440).
Keywords: Dialogues; Motion picture acting